Characterization of Bacillus velezensis TJS119 and its biocontrol potential against insect pathogens - Han, Kook-Il; Nam, Young Ho; Hwang, Byung Su; Kim, Jeong Tae; Jung, Jum Oc; Kim, Eunsun; Lee, Mi-Hwa (Frontiers in Microbiology, 2024)
Introduction: The white-spotted flower chafer (Protaetia brevitarsis seulensis), which is widely distributed in Asian countries, is traditionally used in Oriental medicine. However, its larvae are prone to severe damage by green muscardine disease (caused by Metarhizium anisopliae) during breeding. The aim of this study was to characterize Bacillus velezensis TJS119, which has been isolated from freshwater, and investigate its potential as a biocontrol agent against M. anisopliae in insects. Methods: TJS119 was obtained from freshwater samples in the Republic of Korea and was classiﬁed as B. velezensis. We evaluated its in vitro antifungal effect, sequenced the bacterial whole genome, mined genes responsible for the synthesis of secondary metabolites, performed secondary metabolite analysis (Ultra performance liquid chromatography-mass spectrometry, UPLC-MS/MS), and conducted bioassays for determining green muscardine disease control ability. Results: Bacillus velezensis TJS119 inhibited the mycelial growth of M. anisopliae in vitro. The size of the B. velezensis TJS119 genome was estimated to be 3,890,913 bp with a GC content of 46.67% and 3,750 coding sequences. Biosynthetic gene clusters for secondary metabolites with antifungal activity were identified in the genome. Lipopeptides, including fengycin secreted by TJS119 exhibit antifungal activity. Application of TJS119 for the biocontrol against green muscardine disease increased the viability of white-spotted flower chafer by 94.7% compared to the control. Discussion: These results indicate that B. velezensis TJS119 is a potential biocontrol agent for insect pathogens.